2020
DOI: 10.1186/s13045-020-00909-y
|View full text |Cite|
|
Sign up to set email alerts
|

The lncRNA LAMP5-AS1 drives leukemia cell stemness by directly modulating DOT1L methyltransferase activity in MLL leukemia

Abstract: Background: Mixed-lineage leukemia (MLL) gene rearrangements trigger aberrant epigenetic modification and gene expression in hematopoietic stem and progenitor cells, which generates one of the most aggressive subtypes of leukemia with an apex self-renewal. It remains a challenge to directly inhibit rearranged MLL itself because of its multiple fusion partners and the poorly annotated downstream genes of MLL fusion proteins; therefore, novel therapeutic targets are urgently needed. Methods: qRT-PCR, receiver op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 62 publications
0
40
0
Order By: Relevance
“…Growing studies have uncovered the characteristics of these ncRNAs, including their origins, mechanisms of generation, structures, and potential functions [6,8,12], which can be summarized into a principle for the identification of known species of ncRNAs or even novel ncRNA discovery. As many ncRNAs exhibit highly tissue-specific expression patterns and important roles in biological processes related to cancer [13][14][15][16][17][18][19], ncRNAs have been considered as ideal therapeutic targets for cancer diagnosis and treatment [20][21][22]. Due to the enormous transcription potential of mammalian genomes and multiple mechanisms of ncRNA generation [8,9,23,24], the ncRNA world is still full of infinite mysteries, in which unknown species of RNAs could play important roles.…”
Section: Introductionmentioning
confidence: 99%
“…Growing studies have uncovered the characteristics of these ncRNAs, including their origins, mechanisms of generation, structures, and potential functions [6,8,12], which can be summarized into a principle for the identification of known species of ncRNAs or even novel ncRNA discovery. As many ncRNAs exhibit highly tissue-specific expression patterns and important roles in biological processes related to cancer [13][14][15][16][17][18][19], ncRNAs have been considered as ideal therapeutic targets for cancer diagnosis and treatment [20][21][22]. Due to the enormous transcription potential of mammalian genomes and multiple mechanisms of ncRNA generation [8,9,23,24], the ncRNA world is still full of infinite mysteries, in which unknown species of RNAs could play important roles.…”
Section: Introductionmentioning
confidence: 99%
“…We reported that lnc-eRNAs, such as SEELA, are tethered by histone H4 and act as the “assistants” to bind BRD4, facilitating the activation of SERINC2 by the MLL-BRD4 complex. Our results suggested that lnc-eRNAs are the pivotal mediators of MLL-BRD4-driven oncogene activation, highlighting the potential roles of dysregulated lncRNAs in MLL leukemia progression [ 28 , 60 ]. Furthermore, targeting metabolism is becoming an important strategy for treating diverse cancers [ 61 ], and several lncRNAs have been reported to be associated with metabolic pathways [ 62 , 63 ].…”
Section: Discussionmentioning
confidence: 98%
“…LncRNA can exert its functions through various ways, such as transcriptional or post‐transcription modification and epigenetic change 4,5 . Notably, there are so many studies showing that lncRNA can function through acting as an miRNA regulator, 13,14 this promotes us to explore whether MCF2L‐AS1 can promote the CSC‐like traits through regulating miRNA activity. We then performed bioinformatic analysis and found that there are several miRNAs with potential binding sites on MCF2L‐AS1, among which miR‐873‐5p attracted our attention as miR‐873‐5p showed a relative higher score and has been shown to suppress the stemness of breast cancer cells 11 .…”
Section: Discussionmentioning
confidence: 99%